Nigeria Content Development and Monitoring Board - Chukwuma, Stephen Alumona; Adebolu, Adetunmbi Moses (MultiTech Publisher, 2024)
The study was to examine and to analyze the significance of motivation, a study of Nigeria Content Development and Monitoring Board. A descriptive survey and random sampling techniques method was used. Data collected using two hundred and ten (210) respondents, using a structured questionnaire which was analyzed using simple percentage and chi-square statistical techniques for test of hypothesis, and various implications were interfered. These are the absent of motivational factors in the organization under study can result into low workers' productivity and performance. Four theories were analyzed, Maslow's hierarchy of needs, hygiene theory, equity theory and expectancy theory, and the study adopted Maslow 's hierarchy of needs theory as the theoretical framework. The study was concluded by laudable suggestions called on the management of Nigeria Content Development and Monitoring Board to structure their organizational motivational packages in such a way that will flow from the bottom to the top in an equitable way as suggested by Maslow's theory of needs with promptness and compliance.